The antiepistemology of organized abuse: Ignorance, exploitation, inaction - Salter, Michael (The British journal of criminology, 2023)
Organized abuse, in which multiple adults sexually abuse multiple children, has an important role to play in the production of child sexual abuse material (CSAM) but has been relegated to the margins of criminological concern. This paper presents the findings of an international survey of 74 adults who described childhood victimization in CSAM and organized abuse, emphasizing the relationship between organized abuse and entrenched ignorance of it. The paper identifies the multiple zones, practices and structures of ignorance that render organized abuse unknowable and advocates for strategic forms of knowledge production in which ignorance features as a provocation towards information-seeking rather than as a defence mechanism against intolerable realities.